Perceptions of male professors and male students towards gender equity policies and practices in a Mexican higher education science and engineering graduate program - Masinire, A.; Sanchez-Cruz, E. (South African Journal of Higher Education, 2020)
One of the critical indicators of a gender equal society is the proportional and balanced representation of male and female in all spheres of life. Within the higher education sector in Mexico, gender transformation and equality is measured through the proxy of increased access of female students in higher education. Such demographic changes are occurring as a response to feminist demands for gender equality. While we acknowledge the physical visibility of female academics and students in higher education, this has not been achieved without opposition from male defenders of the status quo. In this study we examine the perceptions of male students and male faculty with regards to the gender policies and their attitudes to the presence of more female students taking up Sciences and Engineering graduate programs. Focusing on the perspectives of men is crucial in gender issues since transformation which does not involving men will likely be opposed by men in defence of gender privileges. The findings reflect that male academics and students men were caught up in conflicting position of accepting the policies in principle but rejecting them in practice. This contradiction arose from deeply internalized and normalized gender stereotypes which deserve educational attention and pedagogical intervention. Officially, the gender policy has affirmed female access and participation in the Science and Engineering graduate program at NPI. However, cultural and institutional gender regimes have not yet aligned themselves to the new policy framework. The question remains as to whether men can change their perceptions about traditional gender roles and responsibilities in order to leverage gender equity and transformation for women justice. Despite literature that suggests that men should be partakers in the fight for gender equality, findings in this study have no affirmative answer to the question.